Conservative treatment for patients with massive prolapsed lumber intervertebral discs - Islam, M. Nazrul; Alam, S. M. Didarul; Imran, M.; Rahman, M. Sahedur; Hasan, M. Tanveer (International Journal of Research in Orthopaedics, 2022)
Background: The natural history of Lumber hernia of nucleus pulpous is not fully known and absolute indications for surgical intervention cannot be established. Several studies have shown that the most giant discs appear to have the greatest tendency to resolve with conservative treatment. The objective of this study is to investigate whether massive prolapsed discs can be safely managed conservatively once clinical improvement has occurred. Methods: Thirty-five patients were studied by clinical assessments and serial magnetic imaging over 3 years. Patients present with intense sciatica but began to show clinical improvement despite massive disc prolapsed. Clinical assessment included the Lasegue test and neurological improvement. The Oswestry disability index was used to measure function and changes in function. Serial MRI studies allowed the measurement of volume changes of the prolapsed disc material over some time. Results: Initial follow-up at an average of 13.2 months showed that 87% had complete and sustained recovery at the initial follow-up. Only four patients required surgery. The average Oswestry disability index improved from 63% to 20%. Volumetric analysis of serial MRI scans showed an average reduction of 69% in disc size. Conclusions: A massive disc prolapsed can pursue a favourable course. If early progress is shown, the long-term prognosis is very good and even massive disc prolapses can be treated conservatively.